Recognition Strategies of Group 3 Innate Lymphoid Cells - Killig, Monica; Glatzer, Timor; Romagnani, Chiara (Frontiers in Immunology, 2014)
During the early phase of an inflammatory response, innate cells can use different strategies to sense environmental danger. These include the direct interaction of specific activating receptors (actR) with pathogen-encoded/danger molecules or the engagement of cytokine receptors by pro-inflammatory mediators produced by antigen presenting cells (APC) in the course of the infection. These general recognition strategies, which have been extensively described for innate myeloid cells, are shared by innate lymphoid cells (ILC), such as Natural Killer (NK) cells. The family of ILC has recently expanded with the discovery of group 2 (ILC2) and group 3 ILC (ILC3), which play an important role in the defense against extracellular pathogens. Although ILC3 and NK cells share some phenotypic characteristics, the recognition strategies employed by the various ILC3 subsets have been only partially characterized. In this review, we will describe and comparatively discuss how ILC3 sense environmental cues and how the triggering of different receptors may regulate their functional behavior during an immune response.